Germany’s difficulties in becoming a member of the International Astronomical Union - Wielen, Roland (Proceedings of the International Astronomical Union, 2019)
After the foundation of the International Astronomical Union (IAU), it took nearly 32 years until Germany became a national member of the IAU. This unfortunate delay was due to both international politics and discussions within Germany (e.g. about the future role of the Astronomische Gesellschaft). The first Statutes of the IAU of 1919 excluded Germany, Austria and other countries from membership for political reasons. When the IAU Statutes were revised in 1931, Germany’s membership was possible, but could not be realized because of financial problems. In the mean time, German astronomers (as individuals) were often able to attend General Assemblies of the IAU as invited participants and to work in IAU Commissions as members. After World War II, Germany became a member of the IAU in 1951, Austria in 1955. In 1962, East Germany was accepted as an additional member. The reunification of Germany in 1990 clarified this situation. Member of the IAU is now one unified Germany.
Gesehen am 02.05.2020